Integrating quantitative proteomics with accurate genome profiling of transcription factors by greenCUT&RUN. Issue 9 (1st February 2021) - Nizamuddin, Sheikh; Koidl, Stefanie; Bhuiyan, Tanja; Werner, Tamara V; Biniossek, Martin L; Bonvin, Alexandre M J J; Lassmann, Silke; Timmers, HThMarc
Abstract: Genome-wide localization of chromatin and transcription regulators can be detected by a variety of techniques. Here, we describe a novel method 'greenCUT&RUN' for genome-wide profiling of transcription regulators, which has a very high sensitivity, resolution, accuracy and reproducibility, whilst assuring specificity. Our strategy begins with tagging of the protein of interest with GFP and utilizes a GFP-specific nanobody fused to MNase to profile genome-wide binding events. By using a GFP-nanobody the greenCUT&RUN approach eliminates antibody dependency and variability. Robust genomic profiles were obtained with greenCUT&RUN, which are accurate and unbiased towards open chromatin. By integrating greenCUT&RUN with nanobody-based affinity purification mass spectrometry, 'piggy-back' DNA binding events can be identified on a genomic scale. The unique design of greenCUT&RUN grants target protein flexibility and yields high resolution footprints. In addition, greenCUT&RUN allows rapid profiling of mutants of chromatin and transcription proteins. In conclusion, greenCUT&RUN is a widely applicable and versatile genome-mapping technique.